Pengaruh Religiusitas, Transparansi, Kepercayaan, Pendidikan dan Minat Sebagai Variabel Mediasi Terhadap Keputusan Muzakki untuk Membayar Zakat pada Baznas Provinsi NTB. - Muhamad Wahyudi Rabbi; Irwan, M; Moh. Huzaini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study was conducted to investigate the influence of religiosity, transparency, trust, and education on muzakki's decision to pay zakat at BAZNAS NTB, by considering interest as a mediating variable. The research method used is a quantitative approach, with a research population consisting of muzakki in NTB Province and a sample size of 100 respondents. The data analyzed included primary and secondary data. The results of the analysis showed that religiosity, transparency, and education did not have a significant impact other than supporting muzakki's decision. On the other hand, the trust variable has a positive and significant influence. Interest has been proven to be a mediating variable in the relationship between trust and education with muzakki's decision. However, interest failed to mediate the relationship between religiosity and transparency, which also did not show a significant influence on muzakki's decision to pay zakat. In addition, interest has a direct impact on the decision. The R-squared test shows that in a direct relationship, the independent variables can explain 38.3% of the variation in muzakki's decision, while the rest is influenced by factors outside the model. In the indirect relationship mediated by interest, the R-squared value of 37.4% indicates a similar influence from other factors outside the research model.